Hypomenstrual syndrome in adolescent girls as a result of reproductive dysfunction in their mothers: Literature review: Literature review - Artyomenko, V.V.; Nastradina, N.M.; Nitochko, K.O.; Altyieva, M.A. (Reproduktivnaâ èndokrinologiâ, 2021)
In recent years in Ukraine and in the world there has been a clear tendency towards deterioration in the indicators of the somatic health of children and adolescents, that is negatively affects the processes of reproductive health formation and it state in the future. Concern for adolescent girl's health, including their reproductive system, forms an enormous contribution to the society future. That's why big attention is paid to the formation and saving reproductive health of adolescent girls. The period of sexual development is defining in a woman's life and is considered a key moment on the path of reproductive maturity. Today it has been established that the reproductive health formation is influenced by environmental, socio-economic factors and the presence of somatic diseases. Despite the fact that the pathogenetic mechanisms of the reproductive system formation are extremely complex and sensitive to the effects of negative factors, the appearance of destructive factors at this time can disrupt the physiological chain of functioning of the hormonal mechanisms which regulate the reproductive system. Disorders of the menstrual cycle is one of the most common pathological conditions, combining pathogenetically different diseases, which are manifested by a violation of the menstrual duration and frequency, amount of menstrual flow. According to domestic literature, hypomenstrual syndrome (oligomenorrhea, amenorrhea) is in the first place among menstrual dysfunctions in adolescent girls in the structure of gynecological morbidity and is up to 45%. Menstrual irregularities that occur during adolescence often persist into the future, causing infertility, obstetric pathology, perinatal loss and other reproductive health problems during childbearing years. The problem of the menstrual cycle formation has been little studied, but it is socially significant, very relevant and requires further study.Thus, girls with menstrual disorders constitute a group of increased risk of gynecological diseases in women of reproductive age, since many chronic diseases of adults are a protracted pathology of adolescents. Therefore, adolescent girls should be examined and treated by a specialist in pediatric and adolescent gynecology, pediatric endocrinologist, pediatrician and family doctor. В последние годы в Украине и мире наметилась четкая тенденция к ухудшению показателей соматического здоровья детей и подростков, что негативно сказывается на процессах формирования и состоянии репродуктивного здоровья в будущем. Забота о здоровье девочек-подростков, включая их репродуктивную систему, вносит огромный вклад в будущее общества. Поэтому большое внимание следует уделять формированию и сохранению репродуктивного здоровья девочек-подростков. Период полового развития является определяющим в жизни женщины и считается ключевым на пути становления репродуктивной зрелости. Сегодня установлено, что на формирование репродуктивного здоровья влияют экологические, социально-экономические факторы и наличие соматических заболеваний. Ввиду того что патогенетические механизмы формирования репродуктивной системы чрезвычайно сложны и чувствительны к негативным воздействиям, появление деструктивных факторов в это время может нарушить физиологическую цепочку функционирования гормональных механизмов регуляции репродуктивной системы. Нарушение менструального цикла – одно из наиболее частых патологических состояний, сочетающее патогенетически разные заболевания, которые проявляются нарушением продолжительности и частоты менструаций, объема менструальных выделений. По данным отечественной литературы, гипоменструальный синдром (олигоменорея, аменорея) занимает первое место среди нарушений менструального цикла у девочек-подростков в структуре гинекологической заболеваемости – до 45%. Нарушения менструального цикла, возникшие в подростковом периоде, часто сохраняются в будущем, вызывая бесплодие, акушерскую патологию, перинатальные потери и другие нарушения репродуктивного здоровья в детородном возрасте. Проблема формирования менструального цикла мало изучена, но социально значима, очень актуальна и требует дальнейшего изучения. Таким образом, девушки с нарушением менструального цикла составляют группу повышенного риска развития гинекологических болезней у женщин репродуктивного возраста, поскольку многие хронические заболевания взрослых являются результатом затяжной патологии подростков. Поэтому следует проводить обследование и лечение девочек-подростков специалистом детской и подростковой гинекологии, детским эндокринологом, педиатром и семейным врачом. Останніми роками в Україні та світі спостерігається чітка тенденція до погіршення показників соматичного здоров'я дітей і підлітків, що негативно впливає на процеси формування та стан репродуктивного здоров'я в майбутньому. Турбота про здоров'я дівчат-підлітків, включно з їхньою репродуктивною системою, робить вагомий внесок у майбутнє суспільства. Тому слід приділяти велику увагу формуванню та збереженню репродуктивного здоров’я дівчат-підлітків. Період статевого розвитку є визначальним у житті жінки й уважається ключовим на шляху становлення репродуктивної зрілості. Сьогодні встановлено, що на формування репродуктивного здоров’я впливають екологічні, соціально-економічні чинники та наявність соматичних захворювань. Зважаючи на те що патогенетичні механізми формування репродуктивної системи є надзвичайно складними й чутливими до негативних впливів, поява деструктивних чинників у цей час може порушити фізіологічний ланцюг функціонування гормональних механізмів регуляції репродуктивної системи. Порушення менструального циклу є одним із найпоширеніших патологічних станів, що поєднує в собі патогенетично різні захворювання, які проявляються порушенням тривалості та частоти менструацій, обсягу менструальних виділень. Згідно з даними вітчизняної літератури, гіпоменструальний синдром (олігоменорея, аменорея) посідає перше місце серед менструальних порушень у дівчаток-підлітків у структурі гінекологічної захворюваності – до 45%. Порушення менструального циклу, що виникли в підлітковому періоді, часто зберігаються в майбутньому, спричиняючи безпліддя, акушерську патологію, перинатальні втрати та інші розлади репродуктивного здоров'я в дітородному віці. Проблема формування менструального циклу мало вивчена, але соціально значуща, дуже актуальна й потребує подальшого вивчення.Отже, дівчатка-підлітки з порушенням менструального циклу становлять групу підвищеного ризику розвитку гінекологічних хвороб у жінок репродуктивного віку, оскільки багато хронічних захворювань дорослих є результатом затяжної патології підлітків. Тому слід проводити обстеження та лікування дівчаток-підлітків фахівцем дитячої та підліткової гінекології, дитячим ендокринологом, педіатром і сімейним лікарем.